National Health Insurance, Profitability, and Service Quality: Case Study at the Private Hospital in West Java - Andriyani Rahmah Fahriati (Faculty of Economic and Business, 2018)
National health insurance is one of the government programs to facilitate health services for the people. The purpose of this research to determine whether there are effects of National Health Insurance program (JKN) on profitability and service quality at Juanda Kuningan Hospital, of West Java. The method using the paired-t-test to analyze the difference between before and after the National Health Insurance program. The result showed that there is a difference in profitability and service quality between pre and post the implementation of national health insurance program. Gross profit margin measured the profitability, net profit margin, return on total assets, and return on equity. This result means that the value of the company's profitability is better when the program JKN yet takes place in the Juanda hospital. While on the service quality variable it is found that the mean value is higher when the JKN program has conducted at the hospital.DOI: 10.15408/etk.v17i1.7064